Fragmentation and urban segregation from the planning of Latin American cities - Mendoza Garcia, Dario Alberto (2025)
Urban fragmentation and segregation are complex phenomena resulting from urban planning processes, as well as social, economic, and political dynamics. These concepts are closely interconnected but possess specific characteristics that merit analysis from the perspective of urban planning. The objective of this article is to examine the dynamics of urban fragmentation and segregation in Latin America, aiming to identify their causes, consequences, and the impact of urban planning policies on these processes. Through a review of academic sources and a critical analysis of case studies related to the metropolitanization and urban expansion of representative cities in the region, this study explores how social stratification and physical and symbolic barriers shape land use and perpetuate urban inequalities. The findings of this study reveal that urban planning, far from being a solution, exacerbates social and territorial exclusion, consolidating patterns of segregation. In response, the article proposes strategies aimed at fostering socioeconomic diversity, ensuring equitable provision of basic services, creating accessible public spaces, and promoting social mobility, with the goal of building more inclusive, sustainable, and equitable cities.